Moving on, moving back or changing it here and now: Self-revision in student translation processes from L2 and L3 - Antunović, Goranka; Pavlović, Nataša (2009)
The paper aims to investigate student translation processes from the second and third language (L2 and L3), with particular regard to self-revision. The form self-revision takes is considered by some authors to be a feature of “translation style”: Mossop (2000, 2001), for example, distinguishes between four translation styles, and the distinction is based on when in the process revisions occur and how substantial they are. There are indications in previous research that translation styles are related to individual preferences rather than to text types, language pairs or direction of translation. This paper proposes to examine whether this is true of student self-revisions, i.e. whether a link can be established between the source language of their translations on the one hand and the timing and the type of their revisions on the other. The study therefore aims to test the following two hypotheses: a) As regards their timing, i.e. when in the process they occur, student revisions are primarily related to acquired translation styles and not to language pair ; b) The type and quantity of revisions primarily depend on language pair and/or the student’s level of competence in different source languages. The study is designed as a series of experiments involving students translating comparable texts (two sections of the same text of which multiple language versions exist, such as texts produced by EU institutions) from their L2 (English) and L3 (Swedish) into their first language (Croatian). Other source languages will be introduced should it prove necessary. The processes will be recorded with the help of a keystroke logging program (Translog). The data will be analyzed in terms of type and number of revisions, as well as their timing within the translation process.
Projekt MZOS
ENG